The Current State and Usage of European Electronic Cross-border Health Services (eHDSI). - Bruthans, Jan; Jiráková, Klára (Journal of Medical Systems, 2023)
Introduction: European Union intends to enable cross-border health services through a program referred to as "MyHealth@EU". The first main service is the dispensation of medicine by interlinking national electronic prescription systems. The second one is the Patient Summary, which enables providing the basic set of patients' medical data. Methods: The contemporary technical documentation of the project was studied and selected published Key Performance Indicators of the project were analyzed. Where necessary, data were acquired directly from the European Commission. Results: Data from the start of the project (fourth quarter of 2019) until the second quarter of 2022 were analyzed. During this time both the overall number of EU countries with operational cross-border healthcare and their particular abilities in both services have risen. At present, there are eleven countries with capabilities in at least one of the services, of which nine have reported transactions. More countries are in the test phase now and will join the operational phase of the project shortly. Discussion and Conclusion: Nevertheless, the program is still used mostly for testing purposes. It seems that only electronic prescription and dispensation are commonly and widely used so far and only Estonian and Finnish patients usually get their medication dispensed abroad. The rest of the operational countries is still at present missing country pairs with a strong cross-border use case.